Design of a public health emergency equipment system for bioterrorism events in public places based on literature review, scenario analysis and Delphi consultation - Xiaowen SUN; Yongzhong ZHANG; Chao ZHAO; Tianyang DENG; Song BAI (Zhongguo gonggong weisheng)
ObjectiveTo improve the standardization of health emergency equipment at the scene of major public bioterrorism events and to establish a health emergency equipment system for such events. MethodsBased on domestic laws and regulations, domestic and international literature on health emergencies from 2004 to 2023, and survey data on the equipment configuration of domestic health emergency equipment enterprises and relevant emergency response teams, this study first used scenario analysis to explore the functional requirements of health emergency equipment from three aspects: the environment in which bioterrorism events occur, the survival and task requirements of personnel at the scene, and the methods of emergency response. Second, with reference to national standards for the allocation of health emergency equipment, a preliminary plan for the equipment system was determined through literature analysis and market research. Finally, the Delphi method was used to revise and improve the plan. ResultsThe positive coefficient of expert consultation in both rounds was 100%, and the mean coefficient of expert authority was 0.855. The coordination coefficients of the expert opinions were 0.226 and 0.258, respectively (both P < 0.001), indicating a good degree of coordination among the expert opinions. Ultimately, 32 functional units were constructed, including five aspects: investigation, testing, decontamination, protection, and treatment, and a health emergency equipment system for major public bioterrorism events was constructed, consisting of 162 units/sets of instruments or equipment. ConclusionThe constructed medical emergency equipment system has a certain degree of pertinence and reliability and can serve as a reference for the construction of medical emergency team equipment systems and the use of medical emergency equipment at the scene of bioterrorism events.